Analisis Strategi Lead Generation dalam Optimalisasi Customer Acquisition Cost (CAC) pada Digital Marketing Scuto Paint - shilla khairani putri (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study analyzes lead generation strategies in optimizing Customer Acquisition Cost (CAC) in Scuto Paint’s digital marketing within the Indonesian automotive car care industry. The increasingly competitive digital ecosystem requires companies not only to increase the number of leads but also to improve lead quality in order to maintain efficient customer acquisition costs. This study employs a literature review method with a descriptive-analytical approach by examining scientific literature related to digital marketing, lead generation, CAC, lead scoring, Conversion Rate Optimization (CRO), Search Engine Optimization (SEO), and artificial intelligence-based marketing technologies. The findings indicate that content marketing, social media utilization, WhatsApp integration, predictive lead scoring, and the combination of SEO, SEM, and Generative Engine Optimization (GEO) contribute to improving lead quality while reducing customer acquisition costs. In addition, CRO, retargeting, and data analytics support marketing effectiveness and customer experience. The study concludes that CAC optimization is achieved not only through reducing promotional costs but also through data-driven marketing strategies, effective resource allocation, and integrated digital customer experiences to sustain business competitiveness in the digital era.